XingNaoJing, prescription of traditional Chinese medicine, prevents autophagy in experimental stroke by repressing p53-DRAM pathway - Wei, Gang (BMC Complement Altern Med, 2015)
BACKGROUND: Xingnaojing (XNJ), a well known prescription in traditional Chinese medicine, has been used for treatment of stroke in China. However, the effects and mechanisms of XNJ on autophagy are not clear. Here, we used the cell models of autophagy induced by serum-free condition and ischemia stroke in rats to further investigate whether the p53-DRAM pathway is involved in the effects of XNJ on autophagy. METHODS: We used the cell model of autophagy induced by serum-free condition and the rat model of ischemia caused by a middle cerebral artery occlusion (MCAO). The effects of XNJ on p53 transcriptional activity of PC12 cells were evaluated by the luciferase activity assay. The mRNA levels and the expression of p53 and its target autophagy gene DRAM (damage-regulated autophagy modulator) were analyzed respectively by Quantitative-RTPCR and Western blot assay. The activation of autophagy was detected by the levels of autophagy markers, microtubule associated protein light chain 3 (LC3) and p62 by Immunofluorescence and Western blot. p53 inhibitor was used to determine whether p53 is responsible for the effects of XNJ on preventing autophagy. RESULTS: The assay for luciferase activity of p53 promoter indicated that XNJ inhibited p53 transcriptional activity. XNJ reduced the expression of p53 and its target autophagy gene DRAM (damage-regulated autophagy modulator) in serum-free condition PC12 cells and the cortex in MCAO rats. XNJ reduced autophagy of PC12 cells induced by serum-free condition and the cortex in MCAO rats. Furthermore, suppression of p53 by p53 inhibitor significantly reduced the effects of XNJ on the autophagy of PC12 cells in serum-free condition. CONCLUSION: XNJ prevents autophagy in experimental stroke by repressing p53/DRAM pathway. Our findings are therefore of considerable therapeutic significance and provide the novel and potential application of XNJ for the treatment of brain diseases.